DEVELOPMENT OF WEATHER BOX LEARNING MEDIA ON A WEATHER THEME IN CLASS III OF PRIMARY SCHOOL - Annisa Fitria; Dinda Yarshal (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is a type of research that develops theory (research and development) by referring to the ADDIE model which is an extension of Analysis, Design, Development, Implementation, Evaluation. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. media expert validation results obtained a percentage of 80%. This percentage includes